(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the phenomenon of code-switching observed in the speech of bilingual individuals from a pragmatic point of view. The study highlights the main pragmatic functions of code-switching in the communicative process, including its role in expressing emotional states, establishing social distance between communication participants, enhancing speech impact, and organizing discourse. The situational dependence of language choice in bilingual speech is demonstrated using examples.